PENDETEKSIAN GELOMBANG ABNORMAL PADA HASIL REKAMAN ELEKTROENSEFALOGRAFI KASUS EPILEPSI DENGAN MENGGUNAKAN METODE SPECTROGRAM - Siswandari Noertjahjani (MEDIA ELEKTRIKA, 2013)
The application of a digital signal processing to EEG waves is to acquire the shapes of the respective autocorrelation and power spectral density functions, as well as to find the parameters values of the associated specific waves understood as “spikes” and “sharps”. Based on a sufficiently large number of patients with a variety of symptoms, we expect to draw some consistent and distinct relations between the specific forms of the autocorrelations as well as the power spectral densities and their associated diagnostic aspects. The acquired parameters values of the “spikes” and “sharps” are intended to establish a procedure to determine or classify the respective phenomena, automatically with a computer. The research carried out so far was to find the prospect of this digital signal processing on EEG waves to support the doctors’ work in this field.